The Emergence of SARS-CoV-2 Variants With a Lower Antibody Response: A Genomic and Clinical Perspective - Biswas, Suvro; Mahmud, Shafi; Mita, Mohasana Akter; Afrose, Shamima; Hasan, Md. Robiul; Paul, Gobindo Kumar; Shimu, Mst. Sharmin Sultana; Uddin, Md. Salah; Zaman, Shahriar; Park, Moon Nyeo; Siyadatpanah, Abolghasem; Obaidullah, Ahmad J.; et al. (Frontiers in Medicine, 2022)
The emergence of several novel SARS-CoV-2 variants regarded as variants of concern (VOCs) has exacerbated pathogenic and immunologic prominences, as well as reduced diagnostic sensitivity due to phenotype modification-capable mutations. Furthermore, latent and more virulent strains that have arisen as a result of unique mutations with increased evolutionary potential represent a threat to vaccine effectiveness in terms of incoming and existing variants. As a result, resisting natural immunity, which leads to higher reinfection rates, and avoiding vaccination-induced immunization, which leads to a lack of vaccine effectiveness, has become a crucial problem for public health around the world. This study attempts to review the genomic variation and pandemic impact of emerging variations of concern based on clinical characteristics management and immunization effectiveness. The goal of this study is to gain a better understanding of the link between genome level polymorphism, clinical symptom manifestation, and current vaccination in the instance of VOCs.